STUDIES ON THE ADSORPTION OF DYES TO KAOLINITE - Harris R.G.; Johnson B.B.; Wells J.D. (My University, 2006)
The strong adsorption to kaolinite of four polyaromatic, cationic dyes (9-aminoacridine, 3,6-diaminoacridine, azure A and safranin O), which adsorb much less to alumina or silica, was investigated by means of acid-base titrations, measurements of adsorption at varying pH and dye concentration, and by ATR-FTIR spectroscopy. The four dyes adsorb to kaolinite to similar extents, with little change over the pH range 3-10, but at higher pH (above the pKas of the dyes) the adsorption of 9-aminoacridine and 3,6-diaminoacridine decreases, that of azure A increases, and that of safranin O stays approximately constant. Although the dyes adsorb to kaolinite much more strongly than metal ions do, titration and spectroscopic data show that there is only limited chemical interaction between the adsorbed dyes and the kaolinite surface. The results indicate that electrostatic interaction between the dye molecules and the kaolinite surface is necessary for adsorption, but that hydrophobic interactions also contribute. It is proposed that the relatively hydrophobic silica faces of kaolinite, which carry low-density permanent negative charge, facilitate aggregation and adsorption of the positively charged, flat, aromatic dye molecules. Copyright © 2006, The Clay Minerals Society.
Keywords: 3,6-DIAMINOACRIDINE; 9-AMINOACRIDINE; ATR; AZURE A; CLAY; DYE; ISOTHERM; KAOLIN; PREFERENTIAL ADSORPTION; SAFRANIN O